SERIAL KASUS EKSTUBASI FAST-TRACK PADA BEDAH JANTUNG TERBUKA - Hapsari, Paramita Putri; Pratomo, Bhirowo Yudo; Putro, Bambang Novianto (Jurnal Komplikasi Anestesi, 2024)
Fast-track extubation (FTE) has been shown to reduce the incidence of prolonged mechanical ventilation, resulting in shorter hospitalization, lower morbidity, mortality, and hospital costs. We present a case series of fast-track extubation involving two females aged 31 and 33 with Atrial Septal Defect (ASD) and a 33-year-old male with Ventricular Septal Defect (VSD) scheduled for defect closure. These patients were in good clinical condition with normal biventricular function and a low probability of pulmonary hypertension. The anesthesia and surgery procedures proceeded smoothly, with cardiopulmonary bypass time < 90 minutes, aortic cross-clamp time < 60 minutes, no residual shunt, acceptable lactate and blood gas analysis, stable hemodynamic with low doses of vasoactive agents, and adequate analgesia. Following the successful execution of the fast-track extubation protocol in the operating theatre, the patients were transferred to the intensive care unit (ICU) where they received postoperative management. The total ICU length of stay was < 24 hours, demonstrating the safety and efficacy of FTE for simple cardiac procedures and favourable outcomes. This approach is aimed at accelerating patient recovery, reducing complications, and enhancing overall surgical outcomes.